BIOMASS VALUATION IN THE CONTEXT OF SUSTAINABLE AGRICULTURAL DEVELOPMENT IN ROMANIA - Panaitescu, Casen; Stoicescu, Maria; Ponea, Maria-Georgiana; Nancu, Dumitru; Nam Nguyen, Dang (Economics of Agriculture, 2020)
Achieving a sustainable agricultural development in Romania represents a major challenge in adapting to new environmental conditions and ecological efficiency. Agriculture has proven over time to be a sustainable producer of biomass, able to offer both in terms of main production of energy crops, and through secondary production or byproduct. In this context the main aim of the manuscript is to asses and analyzes the biomass valuation in the larger context of sustainable agricultural development in Romania. The results prove that biomass is an eligible candidate in valuing the agricultural potential and develop future mechanism in promoting renewables. Taking into consideration these aspects, the manuscript is in line with the current researches in field analyzing the biomass potential in developing new clean and sustainable energy production.